2014
DOI: 10.3390/md12041876
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomic Analysis of Spatial Variation in Soft Corals

Abstract: Soft corals are common marine organisms that inhabit tropical and subtropical oceans. They are shown to be rich source of secondary metabolites with biological activities. In this work, soft corals from two geographical locations were investigated using 1H-NMR spectroscopy coupled with multivariate statistical analysis at the metabolic level. A partial least-squares discriminant analysis showed clear separation among extracts of soft corals grown in Sanya Bay and Weizhou Island. The specific markers that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…The use of advanced metabolomic techniques to determine baseline physiologic function in corals and study of their responses to disease and environmental stressors can help identify early diagnostic markers of coral health status (Viant et al 2002(Viant et al , 2003Viant 2007;Tjeerdema 2008). Use of emerging NMR-based metabolomic techniques in soft corals from different geographic locations has provided early evidence of the broad usefulness of these methods (He et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The use of advanced metabolomic techniques to determine baseline physiologic function in corals and study of their responses to disease and environmental stressors can help identify early diagnostic markers of coral health status (Viant et al 2002(Viant et al , 2003Viant 2007;Tjeerdema 2008). Use of emerging NMR-based metabolomic techniques in soft corals from different geographic locations has provided early evidence of the broad usefulness of these methods (He et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Here, the application of OPLS-DA to 1D 1 H-NMR data (Table 1) revealed an excessive data adjustment in the model that could be attributed to signal overlap in the 1 H-NMR spectra of soft-coral extracts, which was principally due to olefinic protons of diterpenes and the high-field region between 3.2 and 0.8 ppm having a high density of signals due to terpene methyl, methylene, and methine resonances, revealing that soft coral extracts contain large amounts of terpenoids 56 . The noise present in each spectrum of this type of biological sample hinders the alignment and creation of the bins used to reduce the data dimensionality in the NMR spectrum from several thousand points 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Research in this area has so far been restricted to particular invertebrate species, and there are only a few reports concerning the effects of anthropogenic pressures on the overall bioactivity potential of marine benthic invertebrates, especially in Indonesian tropical coral communities. Previous research has shown that production is negatively related to water quality and positively related to biodiversity of predators and benthic competition (Fleury et al, 2004;Hoover et al, 2008;Januar et al, 2011;He et al, 2014). Thus, the research reported here looked to see if there were any bioactive compound production shifts as reefs degrade and change, and investigated directly whether there is any clear correlation between prevailing environmental conditions and biodiversity, and the bioactivity potential of sponges and soft corals.…”
Section: Introductionmentioning
confidence: 90%